Penerapan Prinsip Ekonomi dalam Penentuan Harga Jual Lada dan Dampaknya terhadap Keuntungan Petani di Lampung Selatan - Ajeng Dini Aulia; Erlin Kurniati (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This study aims to explore the application of economic principles in determining the selling price of pepper and its impact on farmers' profits in South Lampung. The approach used was qualitative with in-depth interviews and observation of pepper farmers in several villages in South Lampung. The data collected were analyzed thematically to identify economic factors that influence pepper selling prices, such as production costs, market demand dynamics, and the role of government policies. The results showed that pepper farmers in South Lampung often experience difficulties in determining a profitable selling price, due to dependence on fluctuating market prices and a lack of understanding of economic principles in cost calculation. The impact of this price uncertainty has an impact on the profits earned by farmers, with some farmers reporting unstable profits. This study provides insight into the importance of understanding economic principles in the management of pepper farming, as well as the need for increased knowledge and policy support to improve farmers' welfare.